2022
DOI: 10.1530/etj-21-0081
|View full text |Cite
|
Sign up to set email alerts
|

Impact of body mass index on short-term outcomes after differentiated thyroid cancer surgery: a nationwide inpatient database study in Japan

Abstract: Introduction Recent studies have shown worse post-operative outcomes following several surgeries in underweight or obese patients. However, the association between body mass index (BMI) and short-term outcomes following thyroid cancer surgery remains unclear because of the small number of patients, deficits in background data known as risk factors (e.g. cancer stage, operative procedure, intraoperative device use and hospital volume) and categorisation of BMI. Methods We identified patients who underwent th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Such a long LOS in Japan is partly explained by the smaller number of care facilities (e.g., nursing homes) compared with other countries (13) ; that is, acute care hospitals often cover postacute care for several days. Regarding postoperative situations, both clinicians and patients would consequently tend to closely monitor surgical wounds and laboratory findings in a hospital setting (31) . A previous study revealed that patients may wish to extend their discharge data even based on superstition (relating to the 6 day lunar calendar that is common in Japan) (32) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a long LOS in Japan is partly explained by the smaller number of care facilities (e.g., nursing homes) compared with other countries (13) ; that is, acute care hospitals often cover postacute care for several days. Regarding postoperative situations, both clinicians and patients would consequently tend to closely monitor surgical wounds and laboratory findings in a hospital setting (31) . A previous study revealed that patients may wish to extend their discharge data even based on superstition (relating to the 6 day lunar calendar that is common in Japan) (32) .…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1 shows that patients were unlikely to be discharged on Sunday, although their families could pick them up having to miss work on weekdays. Both doctors and patients may prefer to check the wound on the next weekday (i.e., Monday) rather than discharge on Sunday without a checkup (31) . Because patients who underwent surgery on Monday were discharged during weekdays, their postoperative LOS would not have been affected by the postoperative Sunday effect.…”
Section: Discussionmentioning
confidence: 99%
“…As the RCS function enables a continuous variable to be analyzed without categorization, information and statistical power are not lost in RCS analysis, unlike general regression analysis, which requires categorization of continuous variables such as BMI [13][14][15][16][17]. In this study, we used 4 points (18.5, 22.0, 25.0, and 30.0 kg/m 2 ) as the knots in the cubic splines to allow for nonlinear dose-response effects of continuous BMI measurement, similar to that in previous studies [29,30]. The splines were restricted to be linear below the rst knot and above the last knot.…”
Section: Discussionmentioning
confidence: 99%
“…We defined general complications as respiratory complications, urinary tract infection, sepsis, heart failure, stroke, acute renal failure, and pulmonary embolism. The definitions of these terms are defined on the basis of the approach used in previous studies [ 7 , 29 ] and are listed in Supplemental Table E1 . The secondary outcomes were the duration of anesthesia, postoperative LOS, total hospitalization cost, and 30-day readmission at the same hospital.…”
Section: Methodsmentioning
confidence: 99%